CONSTRUCTION AND EXPRESSION OF RECOMBINANT PLASMIDS CONTAINING NEPHROPATHOGENIC IBV S1 GENE AND LI-KEY SEGMENT OF CHICKEN MAJOR HISTOCOMPATIBILITY COMPLEX II GENE - R. A. Leghari; B. Fan; J. Bai; C. Wen; S. H. Abro; P. Jiang (Journal of Animal and Plant Sciences, 2015)
Infectious bronchitis virus (IBV) produces highly contagious infectious bronchitis disease (IB) of poultry at all ages around the world. In spite of the proper vaccinations, new IBV strains are emerging at poultry farms in China. In this study, a new nephropathogenic infectious bronchitis virus (XDC-2) strain was isolated from a vaccinated flock showing clinical signs of IBV in Jiangsu province of China. The virus was confirmed by SPF chicken embryo lesions, RT-PCR and S1 gene sequencing. The complete spike (S1) glycoprotein and li-key segment of chicken major histocompatibility complex II gene with Flag tagged were amplified (S1-F and Ii-F) with expected band 1684bp and 705bp, respectively. S1 and Ii gene were cloned into pcDNA3.1 eukaryotic expression vector (pcDNA-S1-F and pcDNA-li-F). Recombinant plasmids were confirmed by colony-PCR, enzyme digestion and sequencing. Further, recombinant plasmids were transfected to baby hamster kidney (BHK-21) cells for protein expression in vitro. Cells lysate were used for immune-blot analysis, S1 and Ii genes were successfully expressed with expected band size of protein molecular weight 61KDa and 26KDa, respectively. In conclusion, recombinant plasmids containing IBV complete S1 gene and chicken MHC II li gene expressed in vitro could be co-administer to immunize the chickens for the prevention and control of nephropathogenic IBV infection.
Keywords: Infectious bronchitis virus; Nephropathogenic; S1 gene; chicken MHC II li gene